2014
DOI: 10.1021/am4037993
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Control of Membrane Permeability of Microcapsules for On-Demand Release

Abstract: We report the use of a simple microfluidic device for producing microcapsules with reversible membrane permeability that can be remotely controlled by application of near-infrared (NIR) light. Water-in-oil-in-water (W/O/W) double-emulsion drops were prepared to serve as templates for the production of mechanically stable microcapsules with a core-shell structure and highly uniform size distribution. A biocompatible ethyl cellulose shell was formed, containing densely packed thermoresponsive poly(N-isopropylacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…Due to the heat tolerance of tumor cells being lower than normal tissue, the temperature in the region 42–47 °C can ablate tumor cells . So the tumor cells are selectively destroyed by loosening cell membranes and denaturing proteins with the localized hyperthermia . Meanwhile, the heat activates gel phase to liquid crystalline phase transition for bio‐membrane, which leads the encapsulated drugs release to kill the tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the heat tolerance of tumor cells being lower than normal tissue, the temperature in the region 42–47 °C can ablate tumor cells . So the tumor cells are selectively destroyed by loosening cell membranes and denaturing proteins with the localized hyperthermia . Meanwhile, the heat activates gel phase to liquid crystalline phase transition for bio‐membrane, which leads the encapsulated drugs release to kill the tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most controlled delivery systems in which stimuli are applied to trigger the release or "on" state, 21,22,42,43 our design signicantly slowed down the release. Unlike most controlled delivery systems in which stimuli are applied to trigger the release or "on" state, 21,22,42,43 our design signicantly slowed down the release.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al reported the use of a microfluidic device for producing microcapsules with reversible membrane permeability that can be remotely controlled by application of near‐infrared light …”
Section: Applications Of Membranes In Microfluidicsmentioning
confidence: 99%